2021
DOI: 10.1007/s12055-021-01215-z
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo lung perfusion: how we do it

Abstract: Lung transplantation is an established treatment for patients with end-stage lung disease. However, a shortage of donors, low lung utilization among potential donors, and waitlist mortality continue to be challenges. In the last decade, ex vivo lung perfusion (EVLP) has expanded the donor pool by allowing prolonged evaluation of marginal donor lungs and allowing reparative therapies for lungs, which are otherwise considered not transplantable. In this review, we describe in detail our experience with EVLP incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
(8 reference statements)
3
10
0
1
Order By: Relevance
“…This finding suggests that having EVLP as an option may modify surgical decision-making, a hypothesis consistent with experiences at other centers: Murala et al 43 reported that knowing EVLP is available at their center, in case it is needed, has allowed their team to consider, travel to evaluate, and accept more extended-criteria lungs. In some cases, those additional organs evaluated were deemed suitable for transplantation without EVLP, thereby increasing donor lung availability because of a system-level change produced by having EVLP available 43 . This phenomenon of “indirect growth” of the donor pool is anecdotally well acknowledged, and is becoming increasingly well described in the literature 44 .…”
Section: Discussionsupporting
confidence: 67%
“…This finding suggests that having EVLP as an option may modify surgical decision-making, a hypothesis consistent with experiences at other centers: Murala et al 43 reported that knowing EVLP is available at their center, in case it is needed, has allowed their team to consider, travel to evaluate, and accept more extended-criteria lungs. In some cases, those additional organs evaluated were deemed suitable for transplantation without EVLP, thereby increasing donor lung availability because of a system-level change produced by having EVLP available 43 . This phenomenon of “indirect growth” of the donor pool is anecdotally well acknowledged, and is becoming increasingly well described in the literature 44 .…”
Section: Discussionsupporting
confidence: 67%
“…43 The functional improvements noted in these lungs after just 7 hours meant that EVLP may be a valuable tool in the near future of lung transplantation 43 EVLP began to emerge as a way to evaluate, repair, and recondition lungs that may not have originally been suitable for transplant. 39,42 Interestingly, EVLP is also expanding its usefulness in the fight against unsuspected PE in donor lungs. As mentioned previously, nearly 30% of transplanted lungs have evidence of PE.…”
Section: Novel Techniques In Lung Transplantationmentioning
confidence: 99%
“…In 2018, the lung transplant wait list had increased nearly 40% over the past decade, with an annual waitlist mortality rate of 7.6% or higher in some studies. 39 40 However, donor lung utilization is lower than any other solid transplantable organ, with only 21% of available lungs actually accepted for transplant. 41 With hopes of increasing the lung donor pool, several institutions have begun extending criteria for transplantable lungs to include the use of marginal donors, donation after cardiac death donors, lobar donors, and donors with a mechanical obstruction (PE), all showing similar outcomes compared with standard donor.…”
Section: Novel Techniques In Lung Transplantationmentioning
confidence: 99%
See 2 more Smart Citations